Decreased frequency of sugar-sweetened beverages intake among young children following the implementation of the health promotion levy in South Africa - H Salome Kruger; Tertia van Zyl; Makama A Monyeki; Cristian Ricci; Ruan Kruger (Public Health Nutrition)
Abstract